Multiple cardiovascular complications of COVID-19 infection in a young patient: a case report - Rasras, Hammam (Pan Afr Med J, 2021)
COVID-19 infection is responsible for many complications, which can lead to a high risk of mortality in some patients. Among them are cardiovascular complications which are classified as the most severe. We report a case of a young woman, with no relevant pathological history, admitted for COVID-19 infection, complicated by myocarditis with severe ventricular dysfunction, cardiogenic shock and a large thrombosis into the left ventricle (LV) that was responsible for a left lower limb ischemia associated with a deep venous thrombosis of right lower limb.